2007
DOI: 10.1007/s12149-007-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse and diffuse-plus-focal uptake in the thyroid gland identified by using FDG-PET: prevalence of thyroid cancer and Hashimoto's thyroiditis

Abstract: Our results suggest that although diffuse FDG uptake usually indicates Hashimoto's thyroiditis, the risk of thyroid cancer must be recognized in both diffuse FDG uptake and diffuse-plus-focal FDG uptake on PET scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 18 publications
2
37
0
1
Order By: Relevance
“…The SUV max of chronic thyroiditis patients (2.76 Ϯ 1.24) was significantly higher than that of normal variants (1.99 Ϯ 0.63; p ϭ .002) [31]. Kurata et al [21] reported that the mean SUV max was 3.5 (range, 1.6 -7.8) in 25 patients with diffuse FDG uptake and a USG diagnosis of Hashimoto's thyroiditis. The mechanism of FDG uptake in Hashimoto's thyroiditis is not well understood.…”
Section: Significance Of Fdg-pet-detected Thyroid Incidentalomas and mentioning
confidence: 95%
See 2 more Smart Citations
“…The SUV max of chronic thyroiditis patients (2.76 Ϯ 1.24) was significantly higher than that of normal variants (1.99 Ϯ 0.63; p ϭ .002) [31]. Kurata et al [21] reported that the mean SUV max was 3.5 (range, 1.6 -7.8) in 25 patients with diffuse FDG uptake and a USG diagnosis of Hashimoto's thyroiditis. The mechanism of FDG uptake in Hashimoto's thyroiditis is not well understood.…”
Section: Significance Of Fdg-pet-detected Thyroid Incidentalomas and mentioning
confidence: 95%
“…Other common differential diagnoses for the diffuse uptake pattern include chronic thyroiditis and Graves' disease [11,18]. In a series reported by Kurata et al [21], they found that, of 1,626 patients undergoing an FDG-PET scan, all 25 (1.5%) patients with diffuse uptake turned out to have Hashimoto's thyroiditis. Kang et al [20] showed that when both the focal and diffuse FDG uptake patterns were correlated with ultrasonography (USG) findings, only 59.5% of those with a diffuse uptake pattern had a corresponding nodule in the lobe on USG, whereas Ͼ99% of those with a focal uptake pattern had a corresponding nodule on USG.…”
Section: Significance Of Fdg-pet-detected Thyroid Incidentalomas and mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many of these patients had already been treated with Lthyroxin before performing the scan. Although diffused 18 F-FDG uptake seems to be quite accurate in confirming the diagnosis of Hashimoto thyroiditis [19,21], a risk of thyroid cancer in both diffuse and combined 18 F-FDG uptake should be kept in mind [18,22]. Additionally, the presence of Hashimoto disease with a large goitre may impair the diagnostic value of 18 FDG PET in primary thyroid lymphoma [20].…”
Section: Allmentioning
confidence: 99%
“…A thyroid lesion with focal 18 F-FDG uptake is likely to be malignant [5][6][7][8][9], whereas diffusely increased uptake in the thyroid gland is associated with several thyroid disorders including chronic thyroiditis, Graves' disease, and diffuse goiter [9][10][11][12][13]. Several studies have reported that incidence of diffusely increased 18 F-FDG uptake in the thyroid gland was 0.6-3.3%.…”
Section: Introductionmentioning
confidence: 99%